Rekonstruksi Mulla Shadra Atas Konsep Muhkâm dan Mutasyâbihât Al-Qur’an (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
The basic principle that the Qur'an has two levels, the material and the spiritual level,is associated with other principles namely Muhkamât and Mutasyâbihâtof al-Qur'an. Mulla Shadra divides two levels of Muhkamât and Mutasyâbihâtof Al-Qur'an although both are in one unit. These two levels are Muhkamât and Mutasyâbihât at the level of tafsir and Muhkamât and Mutasyâbihât at the takwil level. Both are in harmony and unity. Takwil must depart from and remain leaning on tafsir, meanwhile tafsirmust return to the nature of its existence at the level of takwil. The concept of Muhkamât and Mutasyâbihât at the level of tafsirwill return to the analysis of language and literature of the Qur'an. At the tafsir level, the verses that have a definite and clear meaning are called the verse of Muhkamât, whereas the verses which have many possible meanings that likely come with similarity or equivocation (musytarak lafdzi) are called Mutasyâbihât verses. On this occasion, the author attempts to answer fundamental questions regarding some concepts of tafsir that have been discussed by some experts of tafsirthrough criticism from Mulla Shadra related to the concept of Muhkamât and Mutasyâbihâtof Al-Qur'an from the treasury of traditional Ulumul al-Quran